Effects of interactions between quorum sensing and quorum quenching on microbial aggregation characteristics in wastewater treatment: A review. (17th November 2021) - Wang, Xueping; Yu, Deshuang; Chen, Guanghui; Liu, Chengju; Xu, Ao; Tang, Zhihao
Abstract: Due to the increasingly urgent demand for effective wastewater denitrification and dephosphorization systems, there is a need to improve the performance of existing biological treatment technologies. As a bacteria‐level communication mechanism, quorum sensing (QS) synchronizes gene expression in a density‐dependent manner and regulates bacterial physiological behavior. On this basis, the QS‐based bacterial communication mechanism and environmental factors affecting QS are discussed. This paper reviews the influence of QS on sludge granulation, biofilm formation, emerging contaminants (ECs) removal, and horizontal gene transfer in sewage treatment system. Furthermore, the QS inhibition strategies are compared. Based on the coexistence and balance of QQ and QS in the long‐term operation system, QQ, as an effective tool to regulate the growth density of microorganisms, provides a promising exogenous regulation strategy for residual sludge reduction and biofilm pollution control. This paper reviews the potential of improving wastewater treatment efficiency based on QS theory and points out the feasibility and prospect of exogenous regulation strategy. Practitioner Points: The mechanism of bacterial communication based on QS and the environmental factors affecting QS were discussed. The application of QS and QQ in improving the sludge performance of biological treatment systems was described. The significance of QS and QQ coexistence in sewage treatment process was described. Abstract : The QS of microorganisms is conducive to promoting the formation of particles and biofilms. On the contrary, when the QQ is dominant in the system, it can effectively alleviate biofilm pollution. The regulation of QS and QQ is a dynamic process in the long‐term operation of the reactor.